Thermal behaviour of residential buildings in South-East Asia through dynamic simulation - Rilling, Dirk (2006)
Dynamic simulation to determine the thermal behavior of buildings is a helpful tool for design and transient analysis. Due to the fact of geographical location, buildings in Malaysia act like energy storage facilities. This leads to discomfort and a massive deployment of air-conditioning facilities. The current work aims to describe how the cooling load of residential buildings is to be predicted by utilizing a software Energy- Plus. The simulation focuses on the influences of the environment as well as the geographical location on the buildings. In this simulation, simple constructional changes and insulation appliances are applied on two different designs of residential houses. They showed a up to 50% lower cooling load. Results have also indicated a positive impact on the consumption of electrical power. Hence, building simulation is a supportive application and useful for energy efficient design in the pre-design stage, as well as for identifying the energy optimization potentials of existing residential buildings.